Neuroregenerative Strategies after Radical Prostatectomy - Dean, Robert C (MedReviews, LLC, 2005)
Patients with erectile dysfunction (ED) following radical prostatectomy (RP) continue to present to practicing urologists. Although nerve-sparing RP has decreased the rates of ED significantly, new therapies for cavernosal nerve protection and recovery are now being developed. This report discusses the many agents available in neuroregeneration and neuroprotection to aid in the recovery of erectile function. Multiple agents and strategies have been used for neuroprotection and neuroregeneration of the cavernosal nerve following RP and in nerve injury models. Many of these agents display promise for the treatment of impotence. Early treatment for patients recovering from RP is becoming the standard of care. Natural recovery of erections may take as long as 18 to 24 months post RP; however, treatment plans may reduce the time to erectile recovery.